PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN KONSUMEN PADA SHANTY SALON CABANG SUNGAI AMPAL BALIKPAPAN - Rizky Maulina, Yuni; Sukimin, Sukimin; Dedy Deomedes, Stephanus (MEDIA RISET EKONOMI [MR.EKO], 2025)
This research aims to analyze the partial and simultaneous influence of service quality variables (tangibles, reliability, responsiveness, assurance and empathy) on consumer satisfaction at Shanty Salon Sungai Ampal Balikpapan Branch. The type of research used is quantitative research. The number of samples in this study was 270 consumers who carried out hair, face and body care transactions at Shanty Salon, Sungai Ampal Balikpapan Branch. The sampling technique used in this research is probability sampling with simple random sampling. The data analysis used is descriptive analysis and multiple linear regression analysis. The test tools used are instrument testing, classical assumption testing, and hypothesis testing. The results of multiple linear regression analysis show that the variables tangibles, reliability, responsiveness, assurance and empathy have a positive and significant influence on consumer satisfaction, either partially or simultaneously. The empathy variable has the most dominant influence on consumer satisfaction at Shanty Salon Sungai Ampal Balikpapan Branch.